Água para quem? Os meandros da gestão de recursos hídricos no estado do Ceará - Saboia, Andrey Luna (2015)
The water crisis is one of the dimensions of the environmental issue, since it involves a multiplicity of aspects of how societies are structured and relate to nature in time and territory. In this context, the management of water resources is one of the political and scientific agendas privileged to contribute in solving the water crisis. The state of Ceará has emerged as a pioneer in modern government management of water management in Brazil, with previous specific legislation the National Water Resources Policy. From the year 1987, with "Government of Changes," a political process of state of equipment for the systematic management of water resources was initiated through the attraction of capital and integration into globalization. However, water scarcity on which part of Ceará's population is periodically submitted has not been eliminated, is quite evident in this dry cycle. Thus, the overall objective of the research is to analyze the current model of water management in the state of Ceara in the context of corporate restructuring. The theoretical framework uses guiding categories and concepts related to environmental issues, the water crisis, the State, territory, power, conflicts and management of water resources. In the light of historical and dialectical materialism, operational methodology was based on five steps, using documentary research, interviews and fieldwork as the main data collection means. The survey revealed that at the heart of the current model of water management there is intense selectivity of state actions, focusing on the management of supply via water infrastructure for river basins that concentrate the main social and productive sectors plaintiffs. Conflicts over water resources have become frequent in certain territories, generating different dynamics and social conflicts.